Optimization of auto-introduction based fermentation media components for biomass production of Escherichia coli BL21-AI expressing recombinant bromelain - Jamaluddin, Mohd Jamil Aizat; Amid, Azura; Azmi, Azlin Suhaida; Othman, Muhd. Ezza Faiez (2009)
In this study, bromelain, a naturally available therapeutic protease enzyme from pineapple stem, was expressed in Escherichia coli strain BL21-AI using auto-inductionbased fermentation media. Recently, many recombinant proteins efficiently expressed in soluble form in E. coli using this auto-induction approach. Indeed, our preliminary experiment showed that this media was proven to be able in producing a high-density batch culture as claimed. Still, since overall soluble expression level is thought to be both protein and host’s strain specific depending on the type of media used, further optimization step for legitimate optimal production of recombinant bromelain is therefore required. Moreover, to our knowledge, as of now optimization study on performance of the production of recombinant bromelain in E. coli using the autoinduction media has yet been initiated elsewhere in the literature. Statistical analysis of results shows that complex nitrogen sources, carbon sources, buffering salts were indeed significant in increasing the biomass production. The optimized values of these three factors were obtained by RSM based on the result of a face-centered central composite design. Under these proposed optimized medium, the model predicted a biomass productivity of 5.567 g/l and its corresponding recombinant bromelain specific activity was reasonably well at 0.1976 U/mg.